2017
DOI: 10.1002/2016sw001536
|View full text |Cite
|
Sign up to set email alerts
|

A new ionospheric storm scale based on TEC and foF2 statistics

Abstract: In this paper, we propose the I‐scale, a new ionospheric storm scale for general users in various regions in the world. With the I‐scale, ionospheric storms can be classified at any season, local time, and location. Since the ionospheric condition largely depends on many factors such as solar irradiance, energy input from the magnetosphere, and lower atmospheric activity, it had been difficult to scale ionospheric storms, which are mainly caused by solar and geomagnetic activities. In this study, statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 22 publications
10
30
0
Order By: Relevance
“…For TEC validation, we also considered normalized percentage changes of TEC (dTEC[%]_norm = [dTEC[%] − ave_dTEC[%]]/std_dTEC[%]), where ave_dTEC[%] is the average of percentage changes of TEC (dTEC[%]) at a given time and at a given location over the quiet 30 days described above, and std_dTEC[%] is the standard deviation of the average percentage change. The normalized percentage change, dTEC[%]_norm, has the advantage to exclude seasonal, local time, and latitudinal dependences of TEC variability by normalizing the percentage variation using its statistical standard deviation and thus should have mainly storm‐induced variation (Nishioka et al, ). Figure shows an example of dTEC[%] (in red) and dTEC[%]_norm (in blue) at Athens on DOY 076 (between 06 UT and 22 UT).…”
Section: Methodsmentioning
confidence: 99%
“…For TEC validation, we also considered normalized percentage changes of TEC (dTEC[%]_norm = [dTEC[%] − ave_dTEC[%]]/std_dTEC[%]), where ave_dTEC[%] is the average of percentage changes of TEC (dTEC[%]) at a given time and at a given location over the quiet 30 days described above, and std_dTEC[%] is the standard deviation of the average percentage change. The normalized percentage change, dTEC[%]_norm, has the advantage to exclude seasonal, local time, and latitudinal dependences of TEC variability by normalizing the percentage variation using its statistical standard deviation and thus should have mainly storm‐induced variation (Nishioka et al, ). Figure shows an example of dTEC[%] (in red) and dTEC[%]_norm (in blue) at Athens on DOY 076 (between 06 UT and 22 UT).…”
Section: Methodsmentioning
confidence: 99%
“…To the best knowledge of the authors, there is no ionospheric index in the available literature that related the drift velocity with the irregularity/p found are related to the TEC or satellites measurements with the plasma irregularity occurrence ( Nishioka et al, 2017). Additionally, this study confirms that this proposed index can b used to warn the users about the irregularity occurrences, since it was shown that under AV there is at least 15 minutes between V to be greater than 60 minu To the best knowledge of the authors, there is no ionospheric index in the available literature that related the drift velocity with the irregularity/p found are related to the TEC or satellites measurements with the plasma irregularity occurrence ( ).…”
Section: Discussionmentioning
confidence: 99%
“…parameter, considering AV 3 , AV 4 observations in ionograms in the summer of 2009 until 2014 over considering all years for AV ble to observe that the mean , we had the mean , the elapsed time between the V zp peak and the irregularity occurrence is greater than 60 minutes with very high probability (around 50%). To the best knowledge of the authors, there is no ionospheric index in the available literature that related the drift velocity with the irregularity/p found are related to the TEC or satellites measurements with the plasma irregularity occurrence ( Nishioka et al, 2017 used to warn the users about the irregularity occurrences, since it was shown that under AV there is at least 15 minutes between V probability of the ∆t vi to be greater than 60 minu into the products offered by the Embrace program, and it impacts in the Space Weather environment…”
mentioning
confidence: 99%
“…Additionally, the ionospheric indexes found show a relationship between TEC or satellite measurements and plasma irregularity occurrence (Huang et al, 2015;Nishioka et al, 2017). On the other hand, there is no ionospheric index in the available literature that found a relationship between the drift velocity and irregularity/plasma bubble occurrences.…”
Section: Climatological Study Of the Av Index And Spreadmentioning
confidence: 99%
“…Jakowski et al (2012) suggested a disturbance ionosphere index (DIX), which describes the perturbation degree of the ionosphere using global navigation satellite systems (GNSS) data. Recently, Nishioka et al (2017) reported on plasma irregularity occurrences using an index based on total electron content (TEC) measurements. However, an index which correlates to the V z with irregularity/plasma bubble occurrences was not found in the literature.…”
Section: Introductionmentioning
confidence: 99%